Land in Dispute. the Relocation of the Indigenous Peoples of Melipilla, Chile Eighteenth and Nineteenth Centuries - Goicovic-Donoso, I; Armijo-Reyes, A (UNIV NAC COLOMBIA, FAC CIENCIAS HUMANAS, 2020)
The social and political conflicts surrounding the Melipilla indigenous peoples located in Chile s central valley was constant throughout the eighteenth century. The conflict began with the displacement of the Melipilla indigenous people to the Maipo River after the founding of the village of San Jose de Logrono in 1742. Then, throughout the eighteenth century, the Melipilla indigenous people coexisted with new projects of land transfers and reductions promoted by the colonial administration and later by the patriot government of the early nineteenth century. However, the forced relocations to other indigenous peoples villages caused, over time, tension in the relations of coexistence between the peoples, likewise, it promoted the resistance of the population to the local authorities. This work aims to analyze the transfers and attempted relocations of indigenous peoples in the Melipilla party in the cycle that runs between 1750 and 1818 and to identify the manifestations of resistance and adaptation displayed by indigenous communities and local authorities. The study is supported by documentation from the funds of the Captaincy General, the Judiciary and Notaries of Melipilla, which are kept in the National Historical Archives of Chile.